Reproach and Silence from the Perspective of Politeness Theory: Pragmalinguistic Analysis of Gabriel García Márquez’s Diatribe of Love against a Seated Man - Vallejo Zapata, Víctor Julián (Íkala, Revista de Lenguaje y Cultura, 2011)
This article presents some findings of a pragmalinguistic analysis of Gabriel García Márquez’s Diatribe of Love against a Seated Man, specifically those related to politeness theory and conversation analysis. The analysis focuses on reproach and silence, put forward as the unique resource of the drama protagonists, Graciela and her husband. All the utterances consisting of these communicative acts were selected; for reproach, the face-threatening level was established, also distinguishing when it points to the positive face or the negative one; for silence, refusal to comply with the Transition Relevance Place (TRP) and Moves were established. Some conclusions are that reproach works as a speech act that threatens against both images simultaneously; on the other hand, the husband’s silence is communicatively characterized, identifying its meaning despite its devoid of propo-sitional content.